Application of an extended CBBE model with particular reference to private car insurance providers in India. (15th July 2020) - Chatterjee, Joyee
This paper attempts to evaluate a new consumer-based brand equity (CBBE) model, an extension of Netmeyer's CBBE model in the context of private car insurance providers in India. This research evaluates the relationship between various variables such as brand attitude, perceived quality, perceived value, uniqueness of the brand, satisfaction and loyalty intention along with CBBE. This is a primary research using structural equation modelling to examine the data collected from 110 respondents in Delhi and NCR region. Hedonic brand attitude wielded a significant impact on building CBBE as opposed to utilitarian attitude and brand uniqueness. With regards to the latter, considering generic nature of the product offering, owing to IRDA guidelines consumers did not find the brands unique. Other relationships between perceived quality, perceived value, CBBE, satisfaction with the brand and loyalty intention were found significant. This research is limited to only one region and cannot be generalised to the entire country.